The role of admission control in assuring multiple services quality - Carvalho, Paulo (2006)
Considering that network overprovisioning by itself is not always an attainable and everlasting solution, Admission Control (AC) mechanisms are recommended to keep network load controlled and assure the required service quality levels. This article debates the role of AC in multiservice IP networks, providing an overview and discussion of current and representative AC approaches, highlighting their main characteristics, pros and cons regarding the management of network services quality. In this debate, particular emphasis is given to an enhanced monitoring-based AC proposal for assuring multiple service levels in multiclass networks.